2022
DOI: 10.1039/d2cc05466c
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic triose glycolysis promoted by co-catalytic proline and phosphate in neutral water

Abstract: Proline and phosphate promote an near-quantitative aldol reaction between glycolaldehyde phosphate and formaldehyde at neutral pH in water. Our results demonstrate the important role of general acid-base catalysis in water...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…What the above two approaches have in common is that they find plausible routes to synthesize, under mild conditions, most of the molecular constituents of existing metabolic cycles, or analogues, which have been proposed that could be ancient based on phylogenetic analyses and other top-down strategies. Similar non-enzymatic versions of the glycolysis and pentose phosphate pathways have been investigated by Ralser's 75,119,120 and Powner's 121,122 groups, yet in this case they would not lead to a protometabolic cycle but to linear anabolic routes. All these efforts point to the likelihood that, if the molecular species of those ancient cycles were readily available on the prebiotic Earth, the establishment of protometabolic networks should have been feasible and may have played a key role in supporting other chemistries – like the emergence of peptide and oligonucleotide replicators, or of new catalysts to couple and make more efficient the required reactions (see below, Section 4).…”
Section: Protometabolic Scenariosmentioning
confidence: 88%
“…What the above two approaches have in common is that they find plausible routes to synthesize, under mild conditions, most of the molecular constituents of existing metabolic cycles, or analogues, which have been proposed that could be ancient based on phylogenetic analyses and other top-down strategies. Similar non-enzymatic versions of the glycolysis and pentose phosphate pathways have been investigated by Ralser's 75,119,120 and Powner's 121,122 groups, yet in this case they would not lead to a protometabolic cycle but to linear anabolic routes. All these efforts point to the likelihood that, if the molecular species of those ancient cycles were readily available on the prebiotic Earth, the establishment of protometabolic networks should have been feasible and may have played a key role in supporting other chemistries – like the emergence of peptide and oligonucleotide replicators, or of new catalysts to couple and make more efficient the required reactions (see below, Section 4).…”
Section: Protometabolic Scenariosmentioning
confidence: 88%
“…We found that the conversion of formaldehyde 2 and isobutyraldehyde 3 to hydroxypivaldehyde 4 was highly effective at neutral pH and catalyzed by phosphate ( 46 , 47 ). For example, incubating 2 (22 mM) and 3 (17 mM) in phosphate buffer solution (PBS) at pH 7 gave hydroxypivaldehyde 4 (94%) after 2 days at 60°C (fig.…”
Section: Chemoselective Aldol Synthesis Of Hydroxypivaldehyde and Pan...mentioning
confidence: 98%
“…Applications of these reactions range from the L‐proline‐catalysed asymmetric aldol reaction in natural product total synthesis, to the functionalisation of biomolecules for cellular labelling and drug delivery in chemical biology [1,2] . However, despite the seminal work of Hajos, Parrish, MacMillan, List and others on the L‐proline catalysed aldol reaction, organocatalytic reactions also occur in Nature and are thought to have played an important role in the chemistry of the early Earth (Figure 1A&B) [3–5] . For example, the L‐amino acids Ser, Ala, Phe, Val, Leu, Glu and Pro have been shown to catalyse the formose reaction of glycolaldehyde and formaldehyde under prebiotically relevant conditions [6] .…”
Section: Figurementioning
confidence: 99%
“…[1,2] However, despite the seminal work of Hajos, Parrish, MacMillan, List and others on the L-proline catalysed aldol reaction, organocatalytic reactions also occur in Nature and are thought to have played an important role in the chemistry of the early Earth (Figure 1A&B). [3][4][5] For example, the L-amino acids Ser, Ala, Phe, Val, Leu, Glu and Pro have been shown to catalyse the formose reaction of glycolaldehyde and formaldehyde under prebiotically rele-vant conditions. [6] Similarly, AcÀ CysÀ OH has been shown to catalyse the chemo-and regio-selective peptide ligation of AcÀ GlyÀ CN and LÀ Ala-suggesting that organocatalysed amide bond formation played a role in the emergence of proteogenic α-peptides in extant biology.…”
mentioning
confidence: 99%